2017
DOI: 10.1093/europace/eux166
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy and electrical storm: results of the OBSERVational registry on long-term outcome of ICD patients (OBSERVO-ICD)

Abstract: Patients with CRT had a lower incidence of ES when compared with propensity-matched ICD patients. The long-term benefit of CRT seems to be due to the improved haemodynamics, as CRT-responders performed markedly better over a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…It is conceivable that triggering of the arrhythmic episode might have been influenced by other factors such as impaired left ventricular function and the potentially pro-arrhythmic nature of CRT-D itself [8]. However, the fact that the patient was a super CRT-D responder along with the event-free period of nine consecutive years after the device implantation was evidence against these factors having a primary role in triggering the electrical storm [9]; although this cannot be ruled out completely.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that triggering of the arrhythmic episode might have been influenced by other factors such as impaired left ventricular function and the potentially pro-arrhythmic nature of CRT-D itself [8]. However, the fact that the patient was a super CRT-D responder along with the event-free period of nine consecutive years after the device implantation was evidence against these factors having a primary role in triggering the electrical storm [9]; although this cannot be ruled out completely.…”
Section: Discussionmentioning
confidence: 99%
“…In primary prevention patients the incidence of ES reaches about 4% [12, 14, 15] and in secondary prevention 10–40% [6, 7]. Only a few analyses comparing the incidence of ES in patients with ICD and CRT-D have been performed [1517]. The prevalence of ES in ICD vs. CRT-D groups was 7% vs. 0.6%, respectively, even though patients with CRT-D had significantly lower mean left ventricular ejection fraction (LVEF) when compared with ICD patients (21.7 ±11% vs. 34 ±15%) [15].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…This difference was explained by the beneficial influence of resynchronization therapy on the reverse modelling of the left ventricle [16]. Guerra et al found that patients with CRT had a lower incidence of ES compared with propensity-matched ICD patients (5.6% vs. 12.3%) and CRT-D was associated with a 45% relative risk reduction in ES compared with ICD [17].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, CRT has been demonstrated to reduce all-cause mortality [ 53 , 58 ] and HF hospitalization [ 59 , 60 ] ( Table 2 ), while reducing left ventricular volumes, increasing left ventricular ejection fraction, and improving NYHA class, 6-minute walking test, quality of life, and peak oxygen consumption [ 61 ]. Moreover, clinical and echographic response to CRT seems to reduce clustered and unclustered ventricular arrhythmias in a recent propensity-score matched analysis [ 62 ].…”
Section: Cardiac Resynchronization Therapy (Crt)mentioning
confidence: 99%